2022
DOI: 10.1021/acsnano.2c02557
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Switchable, Trifunctional Ceramic–Hydrogel Nanocomposites Enable Full-Lifecycle Security in Practical Battery Systems

Abstract: Thermal runaway (TR) failures of large-format lithium-ion battery systems related to fires and explosions have become a growing concern. Here, we design a smart ceramic–hydrogel nanocomposite that provides integrated thermal management, cooling, and fire insulation functionalities and enables full-lifecycle security. The glass–ceramic nanobelt sponges exhibit high mechanical flexibility with 80% reversible compressibility and high fatigue resistance, which can firmly couple with the polymer–nanoparticle hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…1d, Figure S4, Supporting Information). Similar ribbon-shaped bres have been reported in a wide range of ceramic systems, including ZrO 2 /SiO 2 [30], SnO 2 [31], Fe-Al-Oxides [32], etc., which is believed related to the radial collapse of the hollow nano ber structures [33]. The proposed mechanism is that such ber morphology is most likely formed at the very beginning of the electrospinning process, when the surface of the solution jet dries to form a skin layer that rapidly collapses and changes the ber cross-section from circular to at [34,35].…”
Section: Fabrication Of Azfa By 3d Sol-gel Electrospinningsupporting
confidence: 79%
See 1 more Smart Citation
“…1d, Figure S4, Supporting Information). Similar ribbon-shaped bres have been reported in a wide range of ceramic systems, including ZrO 2 /SiO 2 [30], SnO 2 [31], Fe-Al-Oxides [32], etc., which is believed related to the radial collapse of the hollow nano ber structures [33]. The proposed mechanism is that such ber morphology is most likely formed at the very beginning of the electrospinning process, when the surface of the solution jet dries to form a skin layer that rapidly collapses and changes the ber cross-section from circular to at [34,35].…”
Section: Fabrication Of Azfa By 3d Sol-gel Electrospinningsupporting
confidence: 79%
“…Such small-sized crystallites are connected by small-angle grain boundaries, twin boundaries, and amorphous regions, which scatter the strain and promote stress dissipation to allow large deformation [53]. Moreover, it has been suggested by nite element modeling that nanobelt-shaped bers can lower stress levels better than cylindrical bers [30]. Thus, the at-shaped ber cross-section jointly contributes to its superior exibility.…”
Section: Thermal Stability Of Azfamentioning
confidence: 99%
“…As shown in Fig. 3e, after loading an airflow at a constant rate of 1 m/s upon the Z axis of the structural model, we monitored the velocity distribution of fluid, as well as the von Mises stress and total deformation of the solid resulting from the fluid pressure 48 . The dominant red color in the airflow field suggested that the velocity almost remained unchanged in the aerogels.…”
Section: Stability and Gas-permeation Behaviormentioning
confidence: 99%
“…[29][30][31][32][33] Furthermore, PCMs would become flammable materials with danger by accelerating the thermal runaway propagation once the generated heat exceeds their maximum heat dissipation capacity. [34,35] Water, a commonly used liquid that possesses a large latent heat of liquid-vapor phase transition (≈2260 kJ kg −1 ), has also been considered as an efficient thermal management material. [36] Hydrogels containing water content can achieve an obvious cooling effect by utilizing the water evaporation to take away heat, and their heat dissipation coefficient can be as high as ≈50 W m −2 K −1 .…”
Section: Introductionmentioning
confidence: 99%